Development and validation of a LC/MS method for the determination of Δ9-tetrahydrocannabinol and 11-carboxy-Δ9-tetrahydrocannabinol in the larvae of the blowfly Lucilia sericata: Forensic applications. Issue 6 (December 2015) - Karampela, Sevasti; Pistos, Constantinos; Moraitis, Konstantinos; Stoukas, Vasilios; Papoutsis, Ioannis; Zorba, Eleni; Koupparis, Michalis; Spiliopoulou, Chara; Athanaselis, Sotiris
Abstract: In a number of forensic toxicological cases, Δ 9 -tetrahydrocannabinol (THC) and its metabolite 11-carboxy-delta-9-tetrahydrocannabinol (THCA) are frequently considered as contributor factors to the event. To that, a liquid chromatographic mass spectrometric method is described for the identification and quantitation of THC and its metabolite THCA in the forensically important larvae of L. sericata . Larvae of Lucilia sericata were fortified with varying concentrations of THC and THCA covering the calibration range between 10 and 500 pg/mg. For the isolation of the analytes from larvae, several extraction techniques were evaluated and finally liquid-liquid extraction under acidic pH was selected using hexane-ethyl acetate (50:50, v/v) as extraction solvent. For the chromatographic separation, a Waters Symmetry® C18 analytical column was used while the mobile phase was acetonitrile-ammonium acetate (2 mM) (30:70, v/v). The detection was performed using electrospray ionization source in negative mode (ESI-) and the selected ions monitored were m/z 313 for THC and m/z 343 for THCA. The proposed method which is simple and sufficiently sensitive for the detection of THC and THCA even in a single larva sampling, assisted the investigation of a forensic case. Highlights: First reported method for the determination of THC and THCA in fly larvae of forensic interest. First reported study on different extraction approaches of THC and THCA from fly larvae. The amount of larvae affects the isolation of the analytes. The method facilitated the investigation of Forensic case with cannabis implication.